Efficiency Comparison CRAFT vs. SLP Methods in Production Optimization: Perbandingan Efisiensi Metode CRAFT vs SLP dalam Optimasi Produksi - Auliyak , Mohammad Misbahul; Sindhi Cahyana, Athika (Indonesian Journal of Innovation Studies, 2024)
The research conducted at PT. Carma Wira Jatim aimed to optimize the production area layout due to significant challenges stemming from machine delays and material handling inefficiencies. Through systematic layout planning (SLP) and computerized relative allocation of facilities technique (CRAFT), the study proposed improved layouts using Win QSB software. The results indicated differing efficiencies between the CRAFT and SLP methods, with CRAFT demonstrating a 4.5% reduction in total material handling moments compared to the initial layout, suggesting its superiority in this context. These findings underscore the importance of efficient layout design in mitigating production delays and enhancing operational effectiveness. Further research could explore real-time optimization algorithms to adapt layouts dynamically and investigate the impact of layout improvements on overall productivity and resource utilization. Highlight: Improved layout design enhances production efficiency. CRAFT demonstrates superior material handling optimization. SLP offers systematic planning for layout enhancement. Keywoard: Production Layout Optimization, SLP, CRAFT, Material Handling Efficiency, Operational Effectiveness